CHAMP1 premature termination codon mutations found in individuals with intellectual disability cause a homologous recombination defect through haploinsufficiency - Yujiro Yoshizaki; Yunosuke Ouchi; Dicky Kurniawan; Eisuke Yumoto; Yuki Yoneyama; Faiza Ramadhani Rizqullah; Hiyori Sato; Mirjam Hanako Sarholz; Toyoaki Natsume; Masato T. Kanemaki; Masanori Ikeda; Ayako Ui; et al. (Scientific Reports)
Abstract CHAMP1 (chromosome alignment-maintaining phosphoprotein 1) plays a role in the repair of DNA double-strand breaks (DSBs) by homologous recombination (HR). The CHAMP1 gene is one of the genes mutated in individuals with intellectual disability. The majority of the mutations are premature termination codon (PTC) mutations, while missense mutations have also been reported. How these mutations affect the functions of CHAMP1 has not been clarified yet. Here we investigated the effects of the CHAMP1 mutations on HR. In Epstein-Barr virus-induced lymphoblastoid cells and fibroblasts derived from individuals with CHAMP1 PTC mutations, truncated CHAMP1 proteins of the expected sizes were detected. When DSBs were induced in fibroblasts with PTC mutations, a defect in HR was detected. U2OS cells expressing the CHAMP1 mutants did not show an HR defect in the presence of endogenous wild-type (WT) CHAMP1, whereas they were unable to restore HR activity when CHAMP1 WT was depleted, suggesting that the PTC mutations are loss-of-function mutations. On the other hand, the CHAMP1 mutants with missense mutations restored HR activity when CHAMP1 WT was depleted. In DLD-1 cells, heterozygous depletion of CHAMP1 resulted in an HR defect, indicating haploinsufficiency. These results suggest that CHAMP1 PTC mutations cause an HR defect through a haploinsufficient mechanism, while CHAMP1 missense mutations do not affect the HR function of CHAMP1.